2011
DOI: 10.1118/1.3670377
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of x-ray beams in two commercial multidetector computed tomography simulators: Monte Carlo simulations

Abstract: The authors demonstrate the full MC simulations of two commercial MDCT simulators to characterize their x-ray beams. This study may be useful to establish a patient-specific dosimetry for the MDCT systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…Shown in Table 3 and Table 4, the agreement between the Monte Carlo simulations and the ion chamber measurements for the three site-specific scan protocols available on the two scanners is within 5% for all considered data points. Note that we obtained this absolute dose agreement with our source model derived from a set of measurement data without a priori knowledge of scanner specifications, and our results were comparable to those reported by other groups who carried out full Monte Carlo simulations of x-ray tubes with manufacturers’ specifications incorporated (Jarry et al , 2003; DeMarco et al , 2005; Gu et al , 2009; Lee et al , 2011; Lee et al , 2012; Kim et al , 2012). …”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Shown in Table 3 and Table 4, the agreement between the Monte Carlo simulations and the ion chamber measurements for the three site-specific scan protocols available on the two scanners is within 5% for all considered data points. Note that we obtained this absolute dose agreement with our source model derived from a set of measurement data without a priori knowledge of scanner specifications, and our results were comparable to those reported by other groups who carried out full Monte Carlo simulations of x-ray tubes with manufacturers’ specifications incorporated (Jarry et al , 2003; DeMarco et al , 2005; Gu et al , 2009; Lee et al , 2011; Lee et al , 2012; Kim et al , 2012). …”
Section: Resultssupporting
confidence: 87%
“…Compared to all the early works performing either full Monte Carlo simulations (Kim et al , 2012) or energy spectrum-based Monte Carlo simulations for the CT dose estimation (Jarry et al , 2003; DeMarco et al , 2005; DeMarco et al , 2007; Gu et al , 2009; Ding et al , 2010; Lee et al , 2011; Lee et al , 2012), we have shown that the developed generalized source model is accurate in calculating CT doses in the phantoms and in water for a variety of site-specific scan protocols at two widely-used CT scanners.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The authors assumed that the source spectrum is symmetric about the isocenter in the lateral direction and constant in the axial or Z direction. This has previously been shown to be a reasonable assumption, as the energy fluence per incident particle about the x‐axis is approximately symmetric (22) …”
Section: Methodsmentioning
confidence: 89%
“…Monte Carlo (MC) method has been widely used for simulating x-ray scatter radiation and X-ray imaging [34][35][36]. And the accuracy of many MC simulation packages (e.g.…”
Section: Image Acquisitionmentioning
confidence: 99%